RNA N6-methyladenosine reader IGF2BP3 promotes acute myeloid leukemia progression by controlling stabilization of EPOR mRNA - Fan,Jin; Zhuang,Mengqi; Fan,Wei; Hou,Ming (PeerJ, 2023)
Background N6-methyladenosine (m6A) methylation epigenetically regulates normal hematopoiesis and plays a role in the pathogenesis of acute myeloid leukemia (AML). However, its potential value for prognosis remains elusive. Methods Analysis of the datasets downloaded from The Cancer Genome Atlas and Genotype Tissue Expression databases revealed that the expression level of 20 regulators related to m6A RNA methylation differ between patients with AML and normal individuals. A prognostic risk model with three genes (YTHDF3, IGF2BP3, and HNRNPA2B1) was developed using univariate Cox regression and the least absolute shrinkage and selection operator Cox regression methods. Results This established signature demonstrated good predictive efficacy with an area under the curve of 0.892 and 0.731 in the training cohort and the validation cohort, respectively. Patients with AML and an increased level of Insulin growth factor 2 mRNA binding protein 3 (IGF2BP3) expression exhibited a poor prognosis. IGF2BP3 knockdown significantly induced G0/G1 phase arrest and inhibited cell proliferation, apoptosis, and/or differentiation. Further, the JAK/STAT pathway may be involved in the regulation of EPOR expression by IGF2BP3-mediated m6A RNA methylation. Conclusion These findings indicate that IGF2BP3 plays a carcinogenic role in AML, implying that it can predict patient survival and could be an effective strategy for AML therapy.
Keywords: Acute myeloid leukemia; IGF2BP3; m6A methylation; JAK/STAT; EPOR